Development of Designer Transcription Activator-Like Effector-Based Plant Growth Regulator for Higher Yield in Rice - Tang, Yongchao; Wang, Chunlian; Wang, Fujun; Li, Man; Fang, Yanli; Ji, Zhiyuan; Zhao, Kaijun (Frontiers in Plant Science, 2022)
Recent studies have shown that reprogramming of gene expression in a genome can induce production of proteins enabling yield increase. The transcription activator-like effectors (TALEs) from several species of bacterial Xanthomonas have been extensively studied and a series of research tools such as genome editing tool TALENs and gene expression activators have been developed based on the specific protein-nucleic acid recognition and binding mechanisms of TALEs. In this proof-of principle study, we designed and constructed a designer TALE (dTALE), designated as dTALE-NOG1, to specifically target the promoter of OsNOG1 gene in rice, and demonstrated that this dTALE can be used as a new type of plant growth regulators for better crop growth and harvest. In doing so, the dTALE-NOG1 was transferred into the non-pathogenic Xanthomonas oryzae pv. oryzae (Xoo) strain PH to generate a genetic engineered bacteria (GEB) strain called PH-dtNOG1. Functional verification showed that dTALE-NOG1 could significantly induce the expression of OsNOG1. By spraying cell suspension of PH-dtNOG1 on the rice plants during tillering stage, the transcription level of OsNOG1 was highly enhanced, and the grain number of rice plants was increased by more than 11.40% and the grain yield per plant increased by more than 11.08%, demonstrating that the dTALE-NOG1 was highly effective in enhancing rice yield. This work provided a new strategy for manipulating agronomical traits by reprogramming gene expression in a crop genome.